Qualidade total, saúde e trabalho: uma análise em empresas sucroalcooleiras paulistas - Scopinho, Rosemeire Aparecida [UNESP] (Associação Nacional de Pós-Graduação e Pesquisa em Administração, 2000)
Among rural sugar cane wage earners the predominant conceptions and uniform practices in health are of an individual, biologicist and curative nature. This paper analyses the human resource administrative policy, in an attempt to think upon its implications for the workers, inasmuch as it refers to the understanding of health-illness as a bio-psycho-social process and a basic right of citizenship. The reflection is carried out having as a background the productive restructuration process in progress in the sector, which comprises a set of technical-organisational innovations, especially those concerning the implementation of the total quality programmes as managing strategies to obtain productivity, quality and a reduction in the cost of production. Although the policy for administration of human resources incorporates a humanistic and participatory speech, it does not represent an attitude that outdoes the most traditional methods in work administration. It does not manifest itself in real improvements in the quality of life, and also contributes to making more difficult the worker's organising process. The business practices in health and human resource training, are more linked to work control and its adequacy to quality and productivity needs.

Entre os assalariados rurais canavieiros predominam concepções e práticas em saúde de natureza individual, biologicista e curativa. O artigo analisa a política de gestão de recursos humanos no setor sucroalcooleiro paulista, procurando refletir sobre as suas implicações para os trabalhadores, no que se refere à compreensão da saúde-doença como processo bio-psicossocial e um direito básico de cidadania. A análise focaliza o processo de reestruturação produtiva em curso no setor, que se vale de um conjunto de inovações tecnico-organizacionais, especialmente na implantação dos programas que visam à qualidade total, como estratégias gerenciais para obter aumento de produtividade, melhora na qualidade e redução dos custos de produção. A política de gestão de recursos humanos, aparentemente humanista e participativa, não supera os mais tradicionais métodos de gestão do trabalho, não se traduz em melhorias reais na qualidade de vida, e ainda contribui para dificultar o processo organizativo dos trabalhadores. As práticas empresariais em saúde e formação de recursos humanos objetivam o controle e adequação do trabalho às exigências de produtividade e qualidade.
Keywords: work organization; total quality; health; safety at work; organização do trabalho; qualidade total; saúde; segurança no trabalho